Global partnership in the field of human development In the light of Islamic thought (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and the best prayers and peace be upon our master Muhammad and his family and companions.And after:Human development and partnership in it are among the priorities of the Islamic approach, as the follower of the Qur’anic addressee notices a clear focus on the effects of development, and the consequent virtues and good qualities that contribute to building a successful society by all standards. And love between individuals, so God commanded His Prophet to call people to justice and moderation, and to do justice to the oppressed, and to support the weak, and to fight illiteracy, ignorance, backwardness, sickness, leisure, laziness, and unemployment, and he calls to worship God and not associate with Him, and not to take each other as lords besides God, for every religion Heavenly is not different from the other in proving the monotheism and divinity of God Almighty, just as the heavenly religions renounce the enslavement and humiliation of people, and fight persecution, suppression of freedoms and waste of energies carried out by tyrants and tyrants.And human development: a science concerned with the study of what elevates and elevates man, and stimulates his material and moral “spiritual” energies. I have divided this research into an introduction, three demands, and a conclusion, which I describe as follows:The first requirement: defining development and partnership and clarifying their concept in the light of Islamic thought. The second requirement: the foundations of human development in Islamic thought. The third requirement: the global partnership in the field of human development and its importance in solving problemsContemporary.